Pengembangan Media Pembelajaran Baamboozle Materi Lingkaran Terintegrasi Model Cooperative Learning Tipe Teams Game Tournament - Lestari, Lisa Puji; Rohmad Wahid Rhomdani (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Universitas Pamulang, Indonesia, 2025)
This study aims to develop educational game-based learning media Baamboozle on the material of circles integrated with the cooperative learning model type Teams Games Tournament (TGT) to improve the quality of mathematics learning in SMA Negeri 5 Jember. This study uses the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate). Data collection techniques are carried out through material and media validation questionnaires by experts and practicality tests by students. Data analysis is carried out using a mixed methods approach that combines quantitative and qualitative data. The results of the study showed that the Baamboozle media was very valid based on the validation of material experts (90%) and media expert validation (90%), and very practical based on the practicality test by students (89%). This media has been proven to be able to create a pleasant learning atmosphere, increase student collaboration, and facilitate understanding of mathematical concepts, especially on the material of circles. Thus, this learning media is considered feasible to be implemented in the learning process and can be used as an innovative alternative in improving student motivation and learning outcomes in mathematics.